Sistem Pendukung Keputusan Penentuan Jurusan Dengan Menggunakan Metode SAW Di SMK Negeri 1 Merangin - Rokhmah, Zakiyatur; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2021)
The process of studying at SMK Negeri 1 Merangin has difficulties in the new admissions team will appear because the data of prospective students is sufficiently processed and available to process data processing criteria and limited to the respective majors still use the system Manual, using Microsoft Excel. Therefore, it is necessary to support the decision-making system SMKN 1 Merangin. Where the results and discussions in the Decision Support System (SPK) are based on research that is generally done in the process of determining the course. Research from the decision support system is done using the SAW method using the Unified Modeling Language (UML) modeling tool. This research generates a prototype that can be implemented further into the system so that the support system in determining the direction decisions that can be implemented in SMK Negeri 1 Merangin.